Study on the Influence of Introducing Al Transition Layer on Deuterium Resistance of Al2O3 Coating - Weijing Wang; Qinghe Yu; Xiaopeng Liu; Lei Hao; Jing Mi; Shijie Li; Shuai Li; Zheng Lu; Shanshan Li; Hao Liu (International Journal of Photoenergy)
The Al/Al2O3 composite deuterium barrier was deposited on the polished side of 316 L stainless steel by the method of radio-frequency magnetron sputtering. The influence of the introduction of Al transition layer on the deuterium resistance performance of Al2O3 ceramic coating was studied. The field emission scanning electron microscope (SEM), the grazing incident X-ray diffraction technique (GIXRD), and the auger electron spectroscopy (AES) were used to analyze the microscopic morphology, phase, and element distribution in the depth direction of the Al/Al2O3 coating, and the gas-driver permeation method was used to measure the deuterium permeation behavior of the coating sample. The results show that Al2O3 is amorphous after annealing at 873 K. Due to the oxidation of the Al transition layer, the connection between the coating and the substrate is tightly connected. Under the combined action of permeation temperature and pressure of 873 K and 80 kPa, the deuterium permeability of Al/Al2O3 coating is 6.35×10−14 mol·m-1·s-1·Pa-0.5, which shows that the Al/Al2O3 coating has excellent deuterium permeation resistance. Furthermore, deuterium permeability of the Al/Al2O3 coating was diminished by about 2 orders of magnitude compared with 316 L stainless steel, and it is reduced 2~3 times compared with the single Al2O3 coating sample. The study indicates that the introduction of the Al transition layer can significantly enhance the barrier effect of the Al/Al2O3 coating sample.